ANALISIS PENGARUH ASIMETRI INFORMASI, PENGENDALIAN INTERNAL, PERSEPSI KESESUAIAN KOMPENSASI, MORALITAS INDIVIDU, DAN KETAATAN ATURAN AKUNTANSI TERHADAP KECURANGAN AKUNTANSI - Devy Ervina Indriastuti; Agusdin - -; Animah - - (InFestasi, 2016)
Accounting fraud occurred in the form of misstatement of financial statements, abuse of authority by denying or concealing information by the management accounting in the public sector. This study aims to determine the effect of asymmetry of information, internal control, perception of suitability compensation, individual morality and adherence to accounting rules on the accounting fraud in Central Lombok regency government. A sample of 90 respondents was determined by proportional stratified random sampling consisting of Echelon II, III and IV accounting manager directly or indirectly. Data were analyzed using multiple regression formula with the help of SPSS applications. The study concluded that the asymmetry of information and significant positive effect which means increasing the chances of fraud. Internal control, perception of suitability compensation, individual morality a significant negative effect, it can reduce the chances of accounting fraud effectively. While the observance of accounting rules do not affect the accounting fraud due to the lack of reward and punishment accounting manager of the implementation of the rules set. Suggestions in the study for the government of Central Lombok district need their superiors ketegasam in enforcing a rule to be applied to the subordinates, where there needs to be a clear reward and punishment on the performance of subordinates. For further research is expected to explore other factors that may affect the Accounting Fraud and expand into other areas of research objects that may get different results.